2013
DOI: 10.1660/062.116.0101
|View full text |Cite
|
Sign up to set email alerts
|

Roost-Site Characteristics of the Pallid Bat (Antrozous pallidus) in the Red Hills of Kansas and Oklahoma

Abstract: approved:________________________________________________________There is limited understanding of habitat use by bats in the Great Plains and few steps taken toward their conservation, relative to other wildlife. This gap of knowledge, including specific knowledge of two Species in Need of Conservation (SINC) noted by the state of Kansas in the Red Hills region, must be filled for adequate bat conservation. I investigated bat distribution in relation to encroaching woody vegetation and elevation on both the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The extant bat A. pallidus is a crevice-roosting species utilizing cliffs and rocky canyons and sometimes crevices within caves as temporary night roosts (Twente, 1955; Vaughan and O'Shea, 1976). In the present-day Red Hills region of Oklahoma and Kansas, within 150 km E of the Whisenhunt fossil localities, this species roosts in crevices in the gypsum, sandstone, and shale of canyon walls (Miller and Jensen, 2013). However, these red rock layers and canyons are uncommon on the flat, sod-covered southern high plains today, where the fossils occurred.…”
mentioning
confidence: 99%
“…The extant bat A. pallidus is a crevice-roosting species utilizing cliffs and rocky canyons and sometimes crevices within caves as temporary night roosts (Twente, 1955; Vaughan and O'Shea, 1976). In the present-day Red Hills region of Oklahoma and Kansas, within 150 km E of the Whisenhunt fossil localities, this species roosts in crevices in the gypsum, sandstone, and shale of canyon walls (Miller and Jensen, 2013). However, these red rock layers and canyons are uncommon on the flat, sod-covered southern high plains today, where the fossils occurred.…”
mentioning
confidence: 99%
“…A telemetry study in California showed that pallid bats roosted 5-11 km from the areas in which they foraged (Brown et al, 1997). Miller & Jensen (2013) netted radio-tagged individuals in Kansas and Oklahoma at distances from 120 m to 1.2 km from their day roosts. In northern California foraging individuals of both sexes made nightly foraging flights over 2 km long (Baker et al, 2008).…”
Section: Collecting Methodsmentioning
confidence: 99%